THE ROLE OF SOFT SKILLS OF HUMAN RESOURCES IN THE DIGITAL TRANSFORMATION OF BUSINESS: A SURVEY STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN THE DIRECTORATE OF CIVIL STATUS, PASSPORTS, AND RESIDENCY IN SALAH AL-DIN GOVERNORATE - Hisham Khaled abed; Assist prof Dr. Amer Ali Hamad (Scholars Digest Publishing, 2024)
The study aimed to determine the relationship of the impact of the independent variable (soft skills of human resources) and its dimensions represented by (communication and communication skills, cooperation and teamwork skills, staff development and training skills) in the adopted variable (digital business transformation), and its dimensions represented by(digital data, digital technologies, digital talent management, digital operations), the study relied on the descriptive analytical approach in the interpretation and analysis of data and the questionnaire was used as a main tool for the study in data collection, and in order to achieve the objectives of the study and answer its questions, it was distributed (250) a questionnaire for employees of the Directorate of civil status, passports and residence in Salah Al-Din governorate, and (224) valid forms were recovered for analysis, with a recovery rate of (89.6%), and after examining the questionnaires, it was found that (26) questionnaires were invalid for analysis, and this was done by analyzing the data through the statistical program (SPSS Ver.25) to extract statistical methods. The study reached a set of conclusions, most notably: the results of the study showed that there is a significant correlation and influence between each dimension of soft skills of human resources and the digital transformation of business.
Keywords: Soft Skills of Human Resources, Digital Transformation of Business, Directorate of Civil Status, Passports and Residency in Salah Al-Din Governorate.